2016
DOI: 10.5194/bg-13-5171-2016
|View full text |Cite
|
Sign up to set email alerts
|

Autotrophic component of soil respiration is repressed by drought more than the heterotrophic one in dry grasslands

Abstract: Abstract. Summer droughts projected to increase in central Europe due to climate changes strongly influence the carbon cycle of ecosystems. Persistent respiration activities during drought periods are responsible for a significant carbon loss, which may turn the ecosystem from a sink into a source of carbon. There are still gaps in our knowledge regarding the characteristic changes taking place in the respiration of the different components of the ecosystem in response to drought events.In the present study, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 53 publications
(88 reference statements)
3
23
0
Order By: Relevance
“…During summer in SDS, the Cistus plant community, unable to access deep water, moved to a dormant status in order to maintain turgor. This caused a reduction in photosynthates and substrate availability; however, the observed summer depression of SR was not due to a modification of SR h but to the suppression of autotrophic respiration, as already similarly observed in other ecosystem types under drought [13,58,59], and SR h accounted for almost 100% of SR. Concurrently, a significant increase in WEOC was observed, likely because of the high root mortality occurring in summer in Mediterranean ecosystems [60,61] and the simultaneous photodegradation of surface litter at high irradiance [62,63], which both release high amounts of C into the soil. At the same time, a change in the microbial community assemblage could be detected.…”
Section: Discussionsupporting
confidence: 76%
“…During summer in SDS, the Cistus plant community, unable to access deep water, moved to a dormant status in order to maintain turgor. This caused a reduction in photosynthates and substrate availability; however, the observed summer depression of SR was not due to a modification of SR h but to the suppression of autotrophic respiration, as already similarly observed in other ecosystem types under drought [13,58,59], and SR h accounted for almost 100% of SR. Concurrently, a significant increase in WEOC was observed, likely because of the high root mortality occurring in summer in Mediterranean ecosystems [60,61] and the simultaneous photodegradation of surface litter at high irradiance [62,63], which both release high amounts of C into the soil. At the same time, a change in the microbial community assemblage could be detected.…”
Section: Discussionsupporting
confidence: 76%
“…In the present case study, this mowing effect on the soil respiration was more visible in 2016, compared to 2017 and 2018, because of the limited amount of rainfall that occurred in these latter 2 years that might suppress both the microbial activities [42] and the root respiration [40]. Some studies have reported that mowing has an indirect effect on the soil respiration due to herbage removal and exposure of the soil to higher incident solar radiation, which might stimulate the soil microbial activity due to the soil temperature increase [24].…”
Section: The Effects Of Management Practices On Soil Respirationmentioning
confidence: 56%
“…A role for grasslands in climate change mitigation is widely recognized, and the numerous studies that have been carried out recently testify their importance at the global level [5,24,26,32,[39][40][41]. Future climate scenarios in southern Europe suggest that changes in annual temperatures, precipitation patterns, and atmospheric CO 2 concentrations might negatively alter grassland biodiversity and the associated ecosystem services, including regulating services linked to carbon cycling, especially in areas with low summer rainfall [5,41].…”
Section: Relationships Between Soil Respiration Water Content and Tementioning
confidence: 99%
“…However, from the field observations, plots under drought conditions had very sparse vegetation if not completely bare (Figures 2E,F), suggesting a higher contribution of heterotrophic respiration to the measured CO 2 flux than autotrophic respiration. In support, Balogh et al (2016) found that rhizospheric respiration, a component of autotrophic respiration was highly sensitive to drought. Moreover, Hanson et al (2000), asserts that the root contribution to total soil respiration is higher during the growing season and lower during the dormant periods of the year while allude to the stronger relationship between plant growth and root respiration.…”
Section: Effect Of Drought and Grazing On Soil Carbon Storage And Co mentioning
confidence: 94%